Medium-term outcomes of safe surgery system trabeculectomies. Issue 9 (10th July 2008) - Gale, J; Wells, A P
Abstract : Aim: To assess the safety and success of Safe Surgery System trabeculectomy beyond 3 years. Methods: Consecutive case series of 39 eyes in 32 patients. Trabeculectomy was performed using fornix-based conjunctival flap, standard trabeculectomy punch, adjustable scleral flap sutures and antimetabolite treatment. Primary outcome of surgical failure was defined by two criteria: (A) need for further surgery, glaucoma medications or an intraocular pressure (IOP) >21 mm Hg during >10% of follow-up; or (B) IOP >15 mm Hg for >10% follow-up. A relatively aggressive regime of bleb needling and subconjunctival injections was used postoperatively in an attempt to reduce bleb fibrosis and failure. The mean follow-up was 42 months (range 25–55). Results: The rate of surgical failure was 4.4% per eye-year for criterion A, and 8.0% per eye-year for criterion B. Complications were few and compared favourably with other published series. Conclusion: The Safe Surgery System for trabeculectomy provides excellent IOP control both during the operation and in the short and medium term postoperatively, with few complications or surgical failures.